2021
DOI: 10.1177/09544062211030306
|View full text |Cite
|
Sign up to set email alerts
|

Two modified multiscale modeling approaches for determination of two-phase and hybrid nanocomposite properties

Abstract: In this paper, mechanical properties of thermoset epoxy based two-phase and hybrid nanocomposites containing carbon nanotubes (CNTs), and carbon nano diamond particles (CNPs) are determined using two different multiscale modeling approaches. The effects of resin crosslinking, interphase mechanical properties, and filler agglomeration on nanocomposite mechanical properties are investigated. First, the crosslinking between Diglycidyl ether of bisphenol A (DGEBA) resin and Diethylenetriamine (DETA) hardener is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In line with these advancements, the studies focused on the incorporation of nanofillers in epoxy and evaluated the mechanical properties of nanocomposites using experimental and modeling methods. The research establishes a correlation between experimental findings and numerical simulations, offering comprehensive insights into the overall mechanical performance of the composites 17–19 …”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In line with these advancements, the studies focused on the incorporation of nanofillers in epoxy and evaluated the mechanical properties of nanocomposites using experimental and modeling methods. The research establishes a correlation between experimental findings and numerical simulations, offering comprehensive insights into the overall mechanical performance of the composites 17–19 …”
Section: Introductionmentioning
confidence: 66%
“…The research establishes a correlation between experimental findings and numerical simulations, offering comprehensive insights into the overall mechanical performance of the composites. [17][18][19] In comparison with other nanomaterials, Graphene nanoplatelets (GNPs) have emerged as a promising reinforcing material for developing CFRPs composite with enhanced properties. This is due to their interesting mechanical characteristics, including high modulus and strength, a larger surface area, and good thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The shape and surface area of the nanofiller have a prominent role in the formation of constrained regions in polymer nanocomposites. , The interaction area of the nanofiller with polymer surfaces is reduced for nanomaterials with a lower surface area. In the current study, nanosilica (∼175–225 m 2 /g) and GO (∼2590 m 2 /g) are used.…”
Section: Resultsmentioning
confidence: 99%
“…For effectively investigating the decrease of mechanical properties of nanocomposites due to the cluster phenomenon of nanofillers, the multiscale homogenization modeling strategy based on the molecular dynamics (MD) simulation and continuum mechanics has been developed [17][18][19][20][21][22][23]. Shin et al [17] reported that the mechanical properties of the polymer nanocomposites were degraded, as the gap between the nanoparticles decreased by using the MD simulations.…”
Section: Introductionmentioning
confidence: 99%